Architecting ternary heteronanocomposites Bi2S3/BiOCl@In2S3 and Bi2S3/BiOBr@In2S3 for photocatalytic detoxification of organoarsenic compound - Namasivayam Dhenadhayalan (npj Clean Water)
Abstract Ternary heteronanocomposites Bi2S3/BiOCl@In2S3 and Bi2S3/BiOBr@In2S3 were designed as potent and sustainable photocatalysts and demonstrated their visible light-driven detoxification of the organoarsenic pollutant (carbarsone). A facile wet chemical-based synthesis method was applied to fabricate ternary nanocomposites, and their structural properties were analyzed using several analytical techniques (FETEM, XRD, XPS, etc.). In both nanocomposites, the monodispersed nanorod-structured Bi2S3 and nanosheet-structured In2S3, BiOCl, and BiOBr materials were combined to form multi-structured nanocomposites. Both nanocomposites exhibited good photocurrent responses and lower band gap energies that led to their use as photocatalysts for the degradation of carbarsone. As expected, Bi2S3/BiOCl@In2S3 and Bi2S3/BiOBr@In2S3 displayed excellent catalytic performance, achieving carbarsone degradation within 34 and 20 min, with corresponding higher rate constants of 0.1022 and 0.1572 min− 1, respectively. This enhanced photocatalytic activity arose due to synergistic double Z-scheme heterojunctions originating based on the band energies within nanocomposites, which can increase the inhibition of the photogenerated electrons and holes pair’s recombination and relatively maintain the strong catalytic redox properties. Bi2S3 acts as an interfacial mediator for effective charge separation, whereas In2S3 and BiOCl/BiOBr feasibly generate hydroxyl radical reactive species. Mass spectral analysis was employed to prove the oxidative pathway mechanism wherein hydroxyl radicals effectively degrade carbarsone. Furthermore, these nanocomposites displayed strong structural stability along with sustaining catalytic performance, and insignificant loss during the recycling processes. The integration of visible-light sensitivity with strong oxidative capabilities establishes Bi2S3, In2S3, BiOCl, and BiOBr as excellent candidates for photocatalytic detoxification of pollutants.